The Vascular Surgery Workforce: A Survey of Consultant Vascular Surgeons in the UK, 2014. Issue 4 (April 2015) - Harkin, D.W.; Beard, J.D.; Shearman, C.P.; Wyatt, M.G.
Abstract : Objective: The purpose of this study was to describe the demographics, training, and practice characteristics of consultant vascular surgeons across the UK to provide an assessment of current, and inform future prediction of workforce needs. Methods: A questionnaire was developed using a modified Delphi process to generate questionnaire items. The questionnaire was emailed to all consultant vascular surgeons ( n  = 450) in the UK who were members of the Vascular Society of Great Britain & Ireland. Results: 352 consultant vascular surgeons from 95 hospital trusts across the UK completed the survey (78% response rate). The mean age was 50.6 years old, the majority (62%) were mid-career, but 24% were above the age of 55. Currently, 92% are men and only 8% women. 93% work full-time, with 60% working >50 hours, and 21% working >60 hours per week. The average team was 5 to 6 (range 2–10) vascular surgeons, with 23% working in a large team of ≥8. 17% still work in small teams of ≤3. Over 90% of consultant vascular surgeons perform the major index vascular surgery procedures (aneurysm repair, carotid endarterectomy, infra-inguinal bypass, amputation). While 84% perform standard endovascular abdominal aortic aneurysm repair (EVAR), <50% perform more complex endovascular aortic therapy. The majority of vascular surgeons "like their job" (85%) and are "satisfied" (69%) with their job. 34% of consultant vascular surgeons indicated they were "extremely likely" to retire within the next 10 years. Conclusions: This study provides the first detailed analysis of the new specialty of vascular surgery as practiced in the UK. There is a need to plan for a significant expansion in the consultant vascular surgeon workforce in the UK over the next 10 years to maintain the status quo.